LOD for Architectural Heritage: BIM Modeling for the Solimene Factory (diségno, 2019)
The authors created a BIM model of a significant portion of the Solimene ceramic factory (Vietri, Salerno) based on an unstructured model obtained with phase-shift 3D laser scanning. The components, referred to standardized levels of development (LOD), are placed at the origin of a shared and interoperable workflow, suitable for comparing documents and models for design purposes and dissemination of architectural heritage.
Keywords: H-BIM; LOD; 3D Survey; Technologies; Parametric Modelling; Points Cloud; Interoperability